Yellow - Schuette, Sarah L., 1976- (Mankato, Minn. : A+ Books, 2003)
Text and photographs describe common things that are yellow, including mustard, pencils, and lemonade.
Yellow -- Yellow in nature -- Yellow foods -- Yellow at work -- What yellow does -- Finding yellow -- All about yellow -- Words to know -- Read more -- Internet sites.
Includes bibliographical references (page 31) and index.
107569
Keywords: Yellow -- Juvenile literature; Literature; Juvenile works